PENINGKATAN HASIL BELAJAR MURID MENGGUNAKAN MODEL PROJECT BASED LEARNING (PJBL) PADA PEMBELAJARAN IPAS DI KELAS V SDN 274 MUARA DELANG KABUPATEN MERANGIN - Ayu Wariyanti, Gentis; Shilfia Iraqi, Hana; Fitria, Yanti; Erita, Yeni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low learning outcomes of students in Natural and Social Sciences (IPAS) lessons in grade V at SDN 274 Muara Delang, Merangin Regency. Teacher-centered learning causes students to be less active, and learning outcomes have not reached the Learning Achievement Criteria (KKTP). This study aims to describe the Deep Learning Design (RPM), the implementation of learning, and the improvement of student learning outcomes through the application of the Project Based Learning (PjBL) model. The type of research used is Classroom Action Research (PTK) with qualitative and quantitative approaches. The research subjects are teachers and 27 grade V students at SDN 274 Muara Delang, Merangin Regency. The study is planned in two cycles, including the stages of planning, action implementation, observation, and reflection. Data collection techniques were carried out through observation, tests, and documentation. The expected results of this study are an improvement in the quality of planning and implementation of learning as well as an increase in student learning outcomes in IPAS learning through the application of the Project Based Learning (PjBL) model.